The course of infection caused by Encephalitozoon cuniculi genotype III in immunocompetent and immunodeficient mice - Kotková, Michaela; Sak, Bohumil; Hlásková, Lenka; Kváč, Martin (Experimental parasitology, 2017)
Encephalitozoon cuniculi is probably the most common microsporidia which infects a wide range of vertebrates, including human. So far, four genotypes of this parasite have been identified based on the rRNA internal transcribed spacer variations. The course of infection caused by E. cuniculi III had very massive onset in immunocompetent host characterized by the presence of this parasite in all organs and tissues within one week after peroral infection. Encephalitozoonosis caused by E. cuniculi III had very progressive spreading into all organs within first week post inoculation in immunocompromised SCID mice and led to the death of the host. The experimental treatment with albendazole of immunocompetent BALB/c mice infected with E. cuniculi III have shown very weak effect. Our findings clearly showed that the different course of infection and response to treatment depends not only on the immunological status of the host, but also on the genotype of microsporidia. It could be very important especially for individuals under chemotherapy and transplant recipients of organs originating from infected donors.
Keywords: imunokompetence; imunokompromitovaný pacient; spory hub; Mice, Inbred BALB C; Mice, SCID; Encephalitozoon cuniculi; Encephalitozoonosis; Antifungal Agents; myši SCID; myši; Feces; Genotype; Mice; albendazol; Immunocompromised Host; Spores, Fungal; feces; myši inbrední BALB C; zvířata; Albendazole; Immunocompetence; Animals; genotyp; antifungální látky; encephalitozoonóza